Parasitic contamination in the soil of beaches from Mosqueiro Island, Pará State, Brazil - Azevedo Junior, Juscelino Carvalho de; Moreira, Beatriz Modesta; Carvalho, Kássia Larissa Pinto; Oliveira, Beatriz Lopes de; Carvalho, Kássia Larissa Pinto; Guerra, Sylvia de Fátima dos Santos; Pinto, Laine Celestino (Journal of Health & Biological Sciences, 2021)
Objective: We aimed to evaluate the prevalence of intestinal parasitic in the soil of three beaches of Mosqueiro Island, located in the State of Pará, Brazil, as well as to compare the frequency of helminths and protozoa, pathogenic and non-pathogenic parasites according to the beaches analyzed. Methods: This is a cross-sectional analytical study conducted during August and September 2019, in which 155 soil samples were analyzed by Hoffman’s method. Results: The results showed that 16.1% of samples were contaminated from 61.3% of collection points. Murubira beach and Farol beach presented the highest prevalence of parasites, however, there was no significant difference between beaches. Also, it was observed a predominance of protozoa (63%) and non-pathogenic parasites (55.6%) in analyzed samples, but there was no statistically significant difference according to the investigated location. Endolimax nana 25.9% (7/27) and hookworms 18.5% (5/27) were the most detected parasites on the beaches. Conclusion: Thus, this study showed parasitic contamination on the beaches from Mosqueiro Island, which may be associated with a lack of sanitation infrastructure and personal hygiene in these places. Therefore, these results reinforce the need to adopt educational and preventive measures to reduce parasitic agents.